2019
DOI: 10.3390/nu11092107
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Anthocyanins and Human Health

Abstract: Anthocyanins may contribute to the inverse relationship between fruit and vegetable intake and chronic disease. Anthocyanins are pigments found in plant structures that consist of an anthocyanidin (aglycone) attached to sugar moieties. Anthocyanins may be beneficial for health through effects on cellular antioxidant status and inflammation; however, their underlying mechanisms of action in their protection of chronic diseases are likely complex and require further elucidation. This Special Issue comprises 8 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…Indeed, anthocyanins have even demonstrated a greater antioxidant activity than vitamins C and E in vitro [ 42 ]. However, the exact mechanism that governs their antioxidant effect is still under debate and requires further study [ 69 ]. Despite this mechanistic uncertainty, numerous in vivo and in vitro studies have demonstrated an antioxidative effect of anthocyanins [ 68 , 69 ].…”
Section: Antioxidant Potential and Health Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, anthocyanins have even demonstrated a greater antioxidant activity than vitamins C and E in vitro [ 42 ]. However, the exact mechanism that governs their antioxidant effect is still under debate and requires further study [ 69 ]. Despite this mechanistic uncertainty, numerous in vivo and in vitro studies have demonstrated an antioxidative effect of anthocyanins [ 68 , 69 ].…”
Section: Antioxidant Potential and Health Effectsmentioning
confidence: 99%
“…In a review of health benefits associated with anthocyanin consumption, evidence was provided for the beneficial effects of anthocyanins and their metabolites [ 2 , 68 , 69 ]. Protection of the vascular endothelium can directly and indirectly limit long-term stroke effects, and significantly lower blood pressure [ 68 , 69 ]. Recently, the role of anthocyanin intake on the modulation of gut health—through and independently from the gut microbiome—has been elucidated [ 68 , 69 ].…”
Section: Antioxidant Potential and Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported data from epidemiological studies and from dietary interventions with human participants and animal models suggests that anthocyanins have the potential to decrease the risk of CVD [49][50][51]. In addition, there are numerous reports describing putative biological activities of anthocyanins based on treating, for example, cultured human cells with anthocyanins, typically at supraphysiological concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anthocyanidins were active against night blindness, cancer, obesity and heart diseases [4][5][6][7][8] . In addition, various studies reported beneficial properties on bone health with the dietary intake of anthocyanins, such as delphinidin 4,9 .…”
Section: Introductionmentioning
confidence: 99%